If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + v + -3 = 6v Reorder the terms: 7 + -3 + v = 6v Combine like terms: 7 + -3 = 4 4 + v = 6v Solving 4 + v = 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 4 + v + -6v = 6v + -6v Combine like terms: v + -6v = -5v 4 + -5v = 6v + -6v Combine like terms: 6v + -6v = 0 4 + -5v = 0 Add '-4' to each side of the equation. 4 + -4 + -5v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5v = 0 + -4 -5v = 0 + -4 Combine like terms: 0 + -4 = -4 -5v = -4 Divide each side by '-5'. v = 0.8 Simplifying v = 0.8
| 9y-4=3 | | 10+q=18 | | 4/=9/5-7-4/5 | | 3z-z=21-9 | | 7x-118=-2x+251 | | 4b+5=-4-5b | | m-8=9 | | -3g=9-4g | | 15y=(-75) | | 3x+7+3x+6+3x=3x+3x+4x+5 | | -4-w=-5w | | 7x-15-6x=-8 | | 6=x-15 | | x^2=14.44 | | -81-2x=81+7x | | -4n=-3n+9 | | -4(v+8)=8 | | -8d=-9d+10 | | x/2=-8+5 | | x+48+2x-20+x=180 | | 2x+5=x+40 | | 3X-9+x+47=90 | | 9=3x+6x | | 3X-9+x+47=180 | | 2h=-3h-10 | | 5x+6=8x-3 | | 3-4(5-4)= | | x+40=2x+9 | | 31-(x+7)=7x-8 | | 2(3+x)=5x+54 | | -6x-115=-14x+69 | | 18d+5d-20d=72 |